Fungi associated with roots of healthy-looking Scots pines and Norway spruce seedlings grown in nine Swedish forest nurseries - Ndobe, Ernest Ndobe (SLU/Dept. of Forest Mycology and Plant Pathology, 2012)
Soil fungal diversity is essential in ecosystem functioning. Disturbances in the fungal community as a result of abiotic or biotic factors may lead to diseases in the plants. This thesis work was aimed at investigating fungal species composition in healthy looking Norway spruce and Scots pine seedlings grown in nine Swedish forest nurseries. Two methods were used to identify fungi from the seedling roots; culturing and direct sequencing techniques. For the culturing technique 1800 seedlings were sampled. For the direct sequencing technique, 180 seedlings were sampled. The seedlings sampled originated from 36 different provenances. In our results 58 different fungal species were identified. Culturing technique detected 37 fungal species whereas direct sequencing technique detected 21 of them. The most common fungal species identified by the culturing method were: Phoma muscivora, Phialocephala fortinii, Trichoderma viride, Penicillium spinolusum and Meliniomyces variabilis whereas direct sequencing showed that none of the fungi were predominant. Phoma muscivora and Melioniomyces variabilis appeared frequently in the roots and have not been identified in the Fenoscandian forest nurseries before. From our results the following conclusions were drawn; the direct sequencing and culturing techniques are needed to detect potentially all fungal community as both methods complement each other, similar fungal communities colonize Norway spruce and Scots pine seedlings in the nine different nurseries; there may be differences in fungal community structure that colonize the seedling roots of the nine different nurseries; the nurseries may have an influence in the fungal community composition in the nine different nurseries; the provenances may not have an influence on the fungal community composition; a low fungal diversity is observed in all the nine different nurseries.